An Approach To Assembly Facilities Layout Design Problems Using Simulation - Yusof, Norazian (Universiti Sains Malaysia, 2005)
This project focuses on designing an assembly line. Besides, the effects of different model configuration and number of station reduction on the assembly line are studied. In order to design an assembly line, minimum number of station is use to ensure high station’s and worker’s utilization. The assembly line model is developing using WITNESS simulation software. Four assembly line models with different configuration are built using WITNESS. The aim of the simulation is to find the best design that will be later implemented in reality. Statistical analysis, ANOVA is used to find any significance or insignificance of performance measures for different layout model. Results from the experiment have revealed that model’s configuration influence the line’s performance measure.